(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
Higher education is one of the most important investments in human capital. Dissemination of education after 1990 in Poland caused of quantitative changes in the education sector. Every year increased both the number of tertiary education and the number of graduates. This situation resulted in both positive and negative consequences for the labor market. Certainly decreased the possibility of finding a job in line with the competence of persons with higher education, and having a diploma of higher education does not guarantee finding a well-paid job. The aim of the article is to present the situation of people with higher education on the labor market in the region of Middle Pomerania. The main problem of the research was to answer the question: how "educational boom", particularly visible in education at university level, increased the level of danger the lack of employment in the labor market of the Middle Pomerania in the group with higher education. The analysis used data source BDL GUS aggregated at NUTS 3 and NUTS 4.